Ecuadorian healthcare professionals’ perspectives on attributes of asthma care coordination: a qualitative study - Max Bachmann; Philip Cooper; Carolina Barbosa; Maria Jose Cisneros-Caceres; Emily Granadillo; Adriana Romero-Sandoval; Ana Luiza Barreto de Oliveira; Gabriela Pimentel Pinheiro; Alvaro Cruz; Jose Montalvo-Yepez; Guillermo Gómez-Urrego; Rejane Ferreira; et al. (BMJ Open)
Objective This study explored the attributes of asthma care coordination from the perspective of healthcare professionals at different levels of care in Ecuador.Design Qualitative descriptive study. The Integrated Health Networks Model was the theoretical framework of reference. Narrative analysis was used to identify significant phrases from the interviews.Setting Healthcare professionals involved in the care of patients with asthma in primary care, specialists, emergency and management in three Ecuadorian cities between 2019 and 2021.Participants 25 healthcare professionals participated in semistructured in-depth interviews. Convenience sampling was used.Results Participants highlighted the scarce use of institutional documents for the referral of asthma patients from the first level to specialists and vice versa, duplication of tests and medical prescriptions, and lack of appointment availability that limits access to specialised care. From the first level, they considered that specialists do not return patients and specialists stressed that the first level does not have enough training to follow asthma patients. Managers highlighted the system’s inability to assign appointments on time and failures in administrative processes for follow-up. Emergency professionals did not have access to the medical records of patients suffering from asthma attacks.Conclusions The lack of shared objectives and effective communication between different levels of care for the follow-up of asthma patients were attributes of asthma care coordination perceived by healthcare professionals at different levels of care in Ecuador. The Ecuadorian health system should consider these to improve its performance.